2015
DOI: 10.18067/jbfs.v2i4.64
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia e distribuição de galhas foliares de Anacardium occidentale L. (Anacardiaceae)

Abstract: Galhas são estruturas que exibem associações específicas entre o indutor e a planta hospedeira, onde são evidenciadas modificações morfológicas, anatômicas e químicas dos tecidos vegetais. Objetivou-se descrever a morfologia e a distribuição de galhas foliares de Anacardium occidentale L. (Anacardiaceae). Foram coletadas 294 folhas, da porção apical dos ramos, de indivíduos localizados na Universidade Federal do Tocantins -Campus Araguaína, TO. Foram realizadas análises morfológicas utilizando microscópio este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…For instance, Lebel et al (2008) found that most of galls of gall-midge (Diptera: Cecidomyiidae) developed on the leaf veins and on the basal region, followed by the median and apical regions of the Psychotria barbiflora (Rubiaceae) leaves. Scareli- Santos et al (2015) documented that most of the analysed galls of an unidentified Cecidomyiidae species (Diptera) were distributed mainly between the veins (limbus) and in the secondary vein of the leaves of Anacardium occidentale L. (Anacardiaceae). These facts suggest that gall position in the leaves depends on the sites where more quantity of nutrients is transferred.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lebel et al (2008) found that most of galls of gall-midge (Diptera: Cecidomyiidae) developed on the leaf veins and on the basal region, followed by the median and apical regions of the Psychotria barbiflora (Rubiaceae) leaves. Scareli- Santos et al (2015) documented that most of the analysed galls of an unidentified Cecidomyiidae species (Diptera) were distributed mainly between the veins (limbus) and in the secondary vein of the leaves of Anacardium occidentale L. (Anacardiaceae). These facts suggest that gall position in the leaves depends on the sites where more quantity of nutrients is transferred.…”
Section: Discussionmentioning
confidence: 99%
“…Quando os insetos indutores ovipositam a planta hospedeira, alterações se desenvolvem não só no limbo foliar, mas também em todos os órgãos da planta, sendo desta maneira mais frequente nas folhas. (SCARELI-SANTOS et al, 2015). A ação desses galhadores provocam modificações estruturais nos tecidos vegetais de suas plantas hospedeiras (OLIVEIRA et al, 2006 KLEIN;CARNEIRO et al, 2009;SANTOS et al, 2012…”
Section: Introductionunclassified